2019
DOI: 10.1111/nph.15646
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient exchange in arbuscular mycorrhizal symbiosis from a thermodynamic point of view

Abstract: Summary To obtain insights into the dynamics of nutrient exchange in arbuscular mycorrhizal ( AM ) symbiosis, we modelled mathematically the two‐membrane system at the plant–fungus interface and simulated its dynamics. In computational cell biology experiments, the full range of nutrient transport pathways was tested for their ability to exchange phosphorus (P)/carbon (C)/nitrogen (N) sources. As a result, we obtained a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…The recognition and the maintenance of the symbiosis between plants and AM fungi is complex [13,55]. The signal molecules which mediate the recognition between plants and AM fungi have been identified [15,56].…”
Section: Discussionmentioning
confidence: 99%
“…The recognition and the maintenance of the symbiosis between plants and AM fungi is complex [13,55]. The signal molecules which mediate the recognition between plants and AM fungi have been identified [15,56].…”
Section: Discussionmentioning
confidence: 99%
“…Instead they communicate with each other via the cytosolic concentrations (Vincent et al, 2017; Horaruang et al, 2020). Previous studies have shown that membrane sandwiches exhibit another level of dynamics (Gajdanowicz et al, 2011; Schott et al, 2016; Dreyer et al, 2017; Dreyer et al, 2019). Therefore, nutrient homeostasis was also investigated with respect to these dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, transporter types can be mathematically described, allowing deep insights into the dynamics of transporter networks by computational analyses (Dreyer and Michard, 2020). Computational modelling helped already to better understand guard cell movement (Hills et al, 2012; Blatt et al, 2014), the role of K + gradients in energizing phloem (re-)loading processes (Gajdanowicz et al, 2011; Dreyer et al, 2017), the nutrient exchange in mycorrhizal symbioses (Schott et al, 2016; Dreyer et al, 2019; Nizam et al, 2019), the mechanism and potential consequences of vacuolar excitability (Jaslan et al, 2019; Dindas et al, 2021) and touch-sensitive signaling in trigger hairs of the Venus flytrap (Iosip et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Pattern models are rarely applied at this scale of plant biology, often asking questions about spatiotemporal gene expression or regulation patterns (Geng et al, 2013), or developmental patterning (Di Mambro et al, 2017). Models of cellular processes include circadian clock and signaling (Grima et al, 2018), the cell cycle (Roodbarkelari et al, 2010), gene expression (Greenwood et al, 2019), development and cell fate (van Berkel et al, 2013), membrane batteries (Dreyer et al, 2019), photosynthesis (Brian and Hahn, 1987), and carbon flux through metabolic pathways (Allen et al, 2009;Orth et al, 2010).…”
Section: Signal Transduction Pathwaysmentioning
confidence: 99%